Hubungan Kecerdasan Emosi dan Dukungan Sosial Keluarga Dengan Penyesuaian Sosial Remaja - Ningrum, Novita Dwi, Dr. Sri Lestari, S.Psi.,M.Si, Dr. Nanik Prihartanti, M.Si (2016)
This study aims to demonstrate empirically the relationship of emotional intelligence and social support and social adjustment of adolescents. Subject of research that high school students school Albanna Bali School classes X, XI, and XII numbered 180 students. The method used is quantitative method. The sampling technique using population studies. Methods of data collection using emotional intelligence scale, the scale of family support, and social adjustment scale. Technical analysis of the data using regression analysis. The results of data analysis states there is a positive relationship between emotional intelligence and social support for families with adolescent social adjustment. Contributions of emotional intelligence and social support in the family influence on adolescent social adjustment of 9.5%. Variable aspects of emotional intelligence has a greater influence on the social adjustment of the family social support, whereas the smallest aspect is the influence of social support for families. Implications for educational psychology into an evaluation and takes the role of psychology in an effort to improve adolescent social adjustment.